Final-Year B.Sc. Nursing student’s knowledge and attitude regarding pain management - Ms. Gyan Jyoti; Ms. Komal; Ms. Inu; Ms. Harshlata Peter; Ms. Manu Bala (The Bioscan, 2025)
Pain management is a critical aspect of nursing care, requiring nurses to have sufficient knowledge and appropriate attitudes. Objective: This study aimed to assess the knowledge and attitudes of final-year B.Sc. Nursing students toward pain management. Methods: A descriptive study was conducted among 100 nursing students from various colleges in Haryana. Data were collected using a Student Description Form and the Nurses' Knowledge and Attitudes Survey Regarding Pain (NKASRP). Results: Most of the participants (83%) were aged 22 years or younger. A significant portion (61%) had neither received prior education on pain management nor cared for patients experiencing pain. Despite this, 64% of students felt that their nursing curriculum provided adequate education on pain and its management. However, 43% of students demonstrated poor knowledge and attitudes toward pain management, indicating a considerable gap in understanding and practical application. A statistically significant difference was observed between NKASRP scores and the institution where students were pursuing their final year (p > 0.001). Conclusion: Final-year nursing students generally showed poor knowledge and attitudes regarding pain management. Incorporating more structured and standardized, evidence-based pain management education into undergraduate nursing curricula could significantly enhance the quality of patient care and outcomes.